Rapid changes in Atlantic grey seal milk from birth to weaning – immune factors and indicators of metabolic strain. Issue 1 (December 2017) - Lowe, Amanda; Bawazeer, Sami; Watson, David; McGill, Suzanne; Burchmore, Richard; Pomeroy, P.; Kennedy, Malcolm
Abstract True seals have the shortest lactation periods of any group of placental mammal. Most are capital breeders that undergo short, intense lactations, during which they fast while transferring substantial proportions of their body reserves to their pups, which they then abruptly wean. Milk was collected from Atlantic grey seals (Halichoerus grypus ) periodically from birth until near weaning. Milk protein profiles matured within 24 hours or less, indicating the most rapid transition from colostrum to mature phase lactation yet observed. There was an unexpected persistence of immunoglobulin G almost until weaning, potentially indicating prolonged trans-intestinal transfer of IgG. Among components of innate immune protection were found fucosyllactose and siallylactose that are thought to impede colonisation by pathogens and encourage an appropriate milk-digestive and protective gut microbiome. These oligosaccharides decreased from early lactation to almost undetectable levels by weaning. Taurine levels were initially high, then fell, possibly indicative of taurine dependency in seals, and progressive depletion of maternal reserves. Metabolites that signal changes in the mother's metabolism of fats, such as nicotinamide and derivatives, rose from virtual absence, and acetylcarnitines fell. It is therefore possible that indicators of maternal metabolic strain exist that signal the imminence of weaning.